The effects of the CXCR2 antagonist, MK-7123, on bone marrow functions in healthy subjects. Issue 2 (April 2015) - Hastrup, Nina; Khalilieh, Sauzanne; Dale, David C.; Hanson, Lars G.; Magnusson, Peter; Tzontcheva, Anjela; Tseng, Jack; Huyck, Susan; Rosenberg, Elizabeth; Krogsgaard, Kim
Highlights CXCR2 antagonists such as MK-7123 may be useful anti-inflammatory agents. MK-7123 results in a reversible decline in absolute neutrophil counts (ANC). The mechanism of neutrophil decline is unknown. The effect of MK-7123 on myelopoiesis was evaluated as a mechanism of ANC decline. The decrease in ANC was without measurable myelosuppressive effects.